Głód jako problem ekonomiczny i społeczny w świetle nauczania homiletycznego Jana Chryzostoma - Szczur, Piotr (Vox Patrum, 2018)
The article consists of three parts covering consecutively the question of treating ancient homilies as historic sources, the economic dimension of hunger and food shortages, and finally, their social dimension. The analyses presented show that hunger and food shortages were quite common phenomena in ancient societies and they were intrinsically woven into the fabric of their everyday lives. In his homilies John Chrysostom encouraged his congregation not only to show their social conscience in the face of starving people, but also to help those in need. Describing lives of the poor, especially those suffering from hunger, the preacher pictured them as morally entitled to receiving help. We should though remember that descriptions of destitution in John Chrysostom’s homilies and sermons were quite often exaggerated and designed to serve preacher’s specific purpose. This is the reason why we should approach their analyses with extreme caution and thoroughness. Nevertheless, the information on the issue of hunger given by Chrysostom is still valuable and useful in discovering the reality of social relationships in his time.